Tari Ayun-Ayun Sandur Manduro Jombang - Windrowati, Trinil (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2024)
Analysis of the Movement of the Ayun-Ayun Sandur Manduro Jombang Dance has the aim of wanting to reveal the aesthetic value of the form of motion contained in the Ayun-Ayun Sandur Manduro Jombang Dance. The dancers of Sandur Manduro call this dance as Ayun-Ayun Sembadra, because this dance depicts the character of Sembadra who is beautiful, soft and smooth in language. Some players also refer to her as the daughter of Candrakirana, the wife of Panji Inu Kertapati. Using Agus Tasman's Motion Analysis Framework, including space, energy, time and materials as elements of motion. Energy is a force or source of occurrence of a process (form). Energy in motion as a driver of the process of motion form. Space is a vehicle that has a boundary system. Subjectively the limit is dependent on the range of the horizon of vision. Time is a non-physical discourse as a container for a process. Material is something that will be used to create a shape for a specific purpose. The results obtained are that the Ayun-Ayun Sandur Manduro Jombang Dance finds an aesthetic point where its beauty can be felt.